2015
DOI: 10.1007/s11010-015-2463-6
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of IL-12 expression in patients with chronic hepatitis B is mediated by the PI3K/Akt pathway

Abstract: Hepatitis B virus (HBV) replicates noncytopathically in hepatocytes, but HBV or proteins encoded by HBV genome could induce cytokines, chemokines expression by hepatocytes.IL-12 is a typical proinflammatory cytokine that plays a critical role in host defense against pathogens, including the HBV. However, the role of IL-12 in chronic hepatitis B (CHB) remains unclear. The aims of this study were to detect the expression of IL-12 in CHB patients and explore the molecular mechanism of HBV-induced IL-12 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…During HBV infection, the PI3K/Akt pathway was activated [57]. IL-12, as one of the proin ammatory factors, signi cantly increase in CHB patients and HBVinduced IL-12 expression involved into the activation of the PI3K-Akt pathway [29]. In addition, the evidence has demonstrated that the change of PTEN activity leads to development of CHB by deregulating the PI3K/Akt pathway [58].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During HBV infection, the PI3K/Akt pathway was activated [57]. IL-12, as one of the proin ammatory factors, signi cantly increase in CHB patients and HBVinduced IL-12 expression involved into the activation of the PI3K-Akt pathway [29]. In addition, the evidence has demonstrated that the change of PTEN activity leads to development of CHB by deregulating the PI3K/Akt pathway [58].…”
Section: Discussionmentioning
confidence: 99%
“…Recruiting 3-phosphoinositide dependent kinase-1(PDK1) to cell membrane is regulated by PI3K promoting the activation of protein kinase B(Akt), and forms PI3K/PDK1/Akt signaling pathway [27,28]. The activation of PI3K/Akt pathway also increases IL-12 production, which is a typical proin ammatory cytokine of CHB [29]. Research indicated that the lack or decrease of PTEN caused increase of PI3K [30], thus, elevated the level of PDK1 and Akt in the downstream [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…The medium was supplemented with 10% FBS, 100 IU/mL penicillin, and 100 IU/mL streptomycin. Cells were changed into fresh medium every third day, and split by trypsinization at a confluence of about 90%[15]. AD38 cells, which are a variant of HepG2 cells, express the HBV genome under the control of a tetracycline (Tet)-off promoter.…”
Section: Methodsmentioning
confidence: 99%
“…Pro-inflammatory interleukin-12 (IL-12) signalling is the most significant inflammatory pathway associated with HBx (Table S3). IL-12 is upregulated by HBx via the activation of the PI3K/AKT signalling pathway, which could lead to a chronic inflammatory environment (Wang et al, 2015) .…”
Section: Hbv Genes Associated With Hccmentioning
confidence: 99%